Comparison of Thyristor Regulated Three-Phase Reactors’ Schemes - Zakis, J.; Plataiskalns, O.; Rankis, I. (Elektronika ir Elektrotechnika, 2005)
In the following paper combined L-C scheme of reactive power compensation with Delta and wye connected reactor circuit are compared. There are regulation ranges of the current as well as harmonic content of network current discussed. Using computer modulation we can understand, that delta scheme has wider current regulation range and network current harmonic content is better. In both cases current 5.,7.,11. and 13.harmonics must be noticed. Also approximate equitation of network current RMS value for compensator circuit is made. Approximate equitation gives good congruence with computer modulation results. Ill. 7, bibl. 4 (in English, summaries in Lithuanian, English, Russian).